Exposure to Deoxynivalenol During Pregnancy and Lactation Enhances Food Allergy and Reduces Vaccine Responsiveness in the Offspring in a Mouse Model - Seyed Toutounchi, Negisa; Braber, Saskia; van’t Land, Belinda; Thijssen, Suzan; Garssen, Johan; Kraneveld, Aletta D.; Folkerts, Gert; Hogenkamp, Astrid (Frontiers in Immunology, 2021)
Deoxynivalenol (DON), a highly prevalent contaminant of grain-based products, is known to induce reproductive- and immunotoxicities. Considering the importance of immune development in early life, the present study investigated the effects of perinatal DON exposure on allergy development and vaccine responsiveness in the offspring. Pregnant mice received control or DON-contaminated diets (12.5 mg/kg diet) during pregnancy and lactation. After weaning, female offspring were sensitized to ovalbumin (OVA) by oral administration of OVA with cholera toxin (CT). Male offspring were injected with Influvac vaccine. OVA-specific acute allergic skin response (ASR) in females and vaccine-specific delayed-type hypersensitivity (DTH) in males were measured upon intradermal antigen challenge. Immune cell populations in spleen and antigen-specific plasma immunoglobulins were analyzed. In female CT+OVA-sensitized offspring of DON-exposed mothers ASR and OVA-specific plasma immunoglobulins were significantly higher, compared to the female offspring of control mothers. In vaccinated male offspring of DON-exposed mothers DTH and vaccine-specific antibody levels were significantly lower, compared to the male offspring of control mothers. In both models a significant reduction in regulatory T cells, Tbet+ Th1 cells and Th1-related cytokine production of the offspring of DON-exposed mothers was observed. In conclusion, early life dietary exposure to DON can adversely influence immune development in the offspring. Consequently, the immune system of the offspring may be skewed towards an imbalanced state, resulting in an increased allergic immune response to food allergens and a decreased immune responses to vaccination against influenza virus in these models.